Prevalence of Need of Orthodontic Treatment in 7-16-Year-Old School Children in Udaipur City, India - Pradeep Vishnoi; Tarulatha R. Shyagali; Deepak P. Bhayya (Galenos Yayinevi, 2017)
Objective:The study aimed to estimate the need of orthodontic treatment in 7-16-year-old school children in Udaipur city, India.Methods:This cross sectional study enrolled 1029 subjects (661 males and 368 females) belonging to Udaipur city, Rajasthan, India. Subjects who had not undergone orthodontic treatment were randomly selected. The need for orthodontic treatment was assessed using the Dental Health Component of the Index of Orthodontic Treatment Need (IOTN) by the same calibrated examiner. Collected data were quantitatively analyzed, and the difference pertaining to prevalence between males and females was measured using the chi-square test.Results:A Grade 1 IOTN score was observed in 48.4% of the population. Grade 2 was observed in 22.9% of the population. A significant difference was noted for the prevalence of Grades 1, 2, and 3 between male and female children, with male children showing greater prevalence of malocclusion grades. Grades 4 and 5, which were noted less frequently, did not show a significant difference with respect to sex.Conclusion:A higher percentage of the sample required moderate orthodontic treatment. This necessitates proper education and motivation to undergo orthodontic treatment.